2022
DOI: 10.1111/jan.15484
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review exploring the impact of Electronic Health Records (EHR) on the quality of nurse–patient interactions and communication

Abstract: Aim: To explore how nurses' use of electronic health records impacts on the quality of nurse-patient interactions and communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Although these are important aspects of end-of-life care for neurological patients, the format for documenting them in EHR is yet to be developed which made it unlikely that they would be identified and extracted (Forde-Johnston et al, 2022;Sjöberg et al, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although these are important aspects of end-of-life care for neurological patients, the format for documenting them in EHR is yet to be developed which made it unlikely that they would be identified and extracted (Forde-Johnston et al, 2022;Sjöberg et al, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Of notice is the emphasis that is placed on communication with relatives, and on spirituality. Although these are important aspects of end‐of‐life care for neurological patients, the format for documenting them in EHR is yet to be developed which made it unlikely that they would be identified and extracted (Forde‐Johnston et al, 2022 ; Sjöberg et al, 2021 ). The spectrum of these items is therefore limited in the NEOLCAT.…”
Section: Designing a Data Collection Toolmentioning
confidence: 99%
“…The advent of Electronic Health Record (EHR) has enhanced the critical role KM principles and practices play enhancing the care patients receive. However, Forde‐Johnston et al (2023), in their integrative review, found use of EHR influences the quality of nurse–patient interactions and communication. It hinders face‐to‐face communication, promotes task‐oriented communication and affects communication patterns.…”
Section: Challengesmentioning
confidence: 99%
“…While sources conflict on whether EHRs improve documentation burden or not, redistribution of nursing time requires changes in processes and workflows. 4 8 Nurses also describe an increased workload and cognitive burden following EHR implementation which affects their well-being and practice. 2 , 4 , 5 Though EHR use results in adaptive practice changes, 3 , 6 nurses are largely being ignored in the development and research of these technologies.…”
Section: Introductionmentioning
confidence: 99%
“… 4 8 Nurses also describe an increased workload and cognitive burden following EHR implementation which affects their well-being and practice. 2 , 4 , 5 Though EHR use results in adaptive practice changes, 3 , 6 nurses are largely being ignored in the development and research of these technologies. 9 Further, analyzing healthcare technology, nursing theoretical literature tends to perpetuate the limited “love-hate relationship” between nursing and technology.…”
Section: Introductionmentioning
confidence: 99%